Neuro-Marketing in Islamic Education: An Analysis of Emotional and Spiritual Influences in Parents' Decision to Choose a School - Zackyl Musthofa; Muhammad Kholilurrohman; Ida Kusumawati; Unzilah Khomairotus Shiyamah; Siti Khofsah; Muhammad Durrin Ni’am; Abdullah Abdullah; Faizatul Widat; Muhammad Thoiful Abrar (Universitas Nurul Jadid, 2025)
This study aims to examine the influence of emotional and spiritual factors in parents' decision to choose an Islamic school, with a focus on Madrasah. This study uses a qualitative method with an exploratory-interpretive approach, through in-depth interviews, direct observations, and Focus Group Discussions (FGD) with parents of students and the school. The results of the study showed that parents' decisions were influenced by emotional factors, such as concerns about negative environmental influences, and spiritual factors, which included expectations for the formation of Islamic morals and the blessings of education. The two work simultaneously and complement each other, which leads to the decision to choose a school that not only provides academic education, but also prioritizes religious values. These findings also show that tahfidz Islamic boarding schools are a concrete manifestation of the integration of emotional and spiritual factors in parental decisions. This study concludes that in-depth religious education and strong character development are the main considerations for parents in choosing a school. The implication of this study is that the marketing strategy of Islamic education needs to consider the emotional and spiritual dimensions, in addition to the academic aspect, to attract parents' interest in choosing an educational institution